Kerja Sama Hukum Internasional dalam Penanggulangan Tindak Pidana Perdagangan Orang Antara Indonesia dan Australia - Reny seftiyani; depi sri mulyani; ayu wulandari (Yayasan Lentera Keadilan Cendikia, 2025)
Human trafficking is a serious and complex transnational crime that requires strong international cooperation for effective prevention and eradication. Indonesia and Australia, as geographically proximate nations with close bilateral ties, have engaged in multiple forms of international legal cooperation to combat trafficking in persons (TIP). This study explores the forms of cooperation, policy implementation, and the challenges faced in practice. Employing a normative juridical approach and literature review, the study finds that while bilateral and multilateral cooperation—such as MoUs, participation in the Bali Process, and capacity-building initiatives like AIPJ—have been established, key obstacles remain, including differences in legal systems, weak coordination, and limited resources. The article concludes with strategic recommendations to enhance the effectiveness of international legal cooperation in combating TIP in the Asia-Pacific region.